The plight of the Endangered mountain gazelle Gazella gazella. Issue 5 (10th September 2021) - Yom-Tov, Yoram; Balaban, Amir; Hadad, Ezra; Weil, Gilad; Roll, Uri
Abstract: The Endangered mountain gazelle Gazella gazella was once widespread throughout the Levant. Over the past 100 years its population fluctuated greatly as a result of various anthropogenic threats and disturbances. We review the dynamics of the mountain gazelle throughout this period in Israel, its last remaining stronghold, with c. 5, 000 individuals. During the 20th century Israel's human population increased steadily at an annual rate of 2%; the population density is currently 430 persons per km 2 and is forecast to increase further. This presents an array of threats to the mountain gazelle, including habitat change, fragmentation and isolation by roads, railways and fences, poaching, road kills and predation by increasing populations of natural predators and feral dogs, sustained partly by anthropogenic food waste. These threats may act in synergy to amplify their effects. We present an overview of how these factors acted in the past and are currently threatening the survival of this species. We also review the policy and management actions, both implemented and still required, to ensure the persistence of the mountain gazelle. In addition, we analyse connectivity in the landscape, highlighting highly fragmented gazelle populations, and suggest potential interventions. The mountain gazelle exemplifies an ungulate with both great vulnerability to human pressures and a large breeding potential. As more regions, in Israel and elsewhere, are converted to human dominated landscapes, pressures on wildlife are increasing, and lessons from the mountain gazelle could prove valuable.